Certain syndrome or complex conundrum? : the pollination of Erica lanuginosa - Mitrani, Leila Mical (Department of Biological Sciences, 2017)
The flower of Erica lanuginosa has a tightly closed corolla, held in place by hinged sepals. with a dull reddish-pink colour which makes make it hard to determine a likely pollinator. Rodent trapping and pollen analysis of faecal matter showed it unlikely to be pollinated by a rodent. Flowers excluded from external pollination showed no seed set, hence it is not considered to be self-pollinated. Nectar analysis are inconclusive as an indicator of pollination syndrome. Entomophily by a robust insect with a medium length proboscis is considered unlikely due to phenology and morphology of the flower. Omothiphily is a possibility as stem thickness correlates with previous studies investigating the correlation between stem thickness and pollination syndromes. The pollination syndrome of Erica lanuginosa remains indeterminate by I hypothesize that, due to phenology, thick supportive, stem and large quantities of nectar and close-formed flower, which needs to be manoeuvred open, its pollinator is likely a short-billed generalist-feeding bird restricted by food choice during the winter months.